Health-promoting lifestyles and influencing factors among pregnant women with urinary incontinence: a multicentre cross-sectional study - Ping Xu; Yi Li; Xiaojuan Wang; Minna Mao; Suwen Feng; Huijie Zhou; Shuiqin Gu (BMJ Open)
Objective Lifestyle modification is an important part of non-surgical treatment for urinary incontinence (UI) and is strongly recommended. This study aims to explore the status and influencing factors of health-promoting lifestyle among pregnant women with UI.Design A multicentre cross-sectional study.Setting This study was conducted in obstetric clinics of three tertiary-level A hospitals in Zhejiang Province, mainland China.Participants A total of 519 pregnant women with UI were enrolled in this study from May 2023 to August 2023.Outcome measures Lifestyle Profile Scale for Gravidas with Urinary Incontinence (LPG-UI) was used to assess health-promoting lifestyle status. Multivariate stepwise linear regression analysis was performed to identify significant influence factors.Results Most participants reported mild-to-moderate UI, with over 60% experiencing UI starting from the first and second trimesters. The mean score of LPG-UI was 86.74 (SD=12.75) out of a score of 120. The results of multivariate stepwise linear regression analysis showed that those who had better environmental satisfaction (β=0.22, p<0.001), self-efficacy (β=0.168, p<0.001), social support (β=0.153, p<0.001) and knowledge of UI (β=0.104, p<0.01) have higher levels of health-promoting lifestyles, while those who had worse depression (β=−0.214, p<0.001), fewer exercise before pregnancy (β=−0.135, p<0.001) and physical work (β=−0.076, p<0.05) have lower levels of health-promoting lifestyles. A total of 38.5% variation in the regression equation could be explained.Conclusions The health-promoting lifestyle of pregnant women with UI needs to be further promoted. Governments and the social sector need to do more to improve the accessibility of environments such as sports and healthcare. Meanwhile, increasing the individual health responsibility of pregnant women with UI and promoting help-seeking behaviours are also top priorities. More social and emotional support should be added to improve self-efficacy and positive moods to enhance health promotion lifestyles.